Motivation in ELT classrooms - Janečková, Hana (Univerzita Pardubice, 2008)
This paper deals with the topic of motivation and motivational strategies. The first, theoretical part describes motivation from the theoretical level and thus creates a framework for designing the practical inquiry. The second part presents the findings of the research. The practical part is closely focused on which motivational strategies English language teachers employ in their lessons and with what success.
Motivace v hodinách anglického jazyka
Keywords: Motivace; motivační strategie; Anglický jazyk; vyučování anglického jazyka; Motivation; motivational strategies; English language; English language teaching